اجازة العقد الموقف في القانون المدني العراقي"دراسة مقارنة" "دراسة مقارنة" - الگزنیز, محمد احمد (Sulaimani Journal for Humanities, 2003)
This subject contains two sections, the first one deals with allowance of the halted contracts, in it we concluded that iraqi civilian law is going with Malik creed in the conditions of allowance of the halted contracts and its effects. second section deals with canceling of halted contracts, here we concluded that the law also took the Malik creed espesially in the setting of purchasers with innocent intention, because it gives that type of purchasers the right to take the benefits from receiving till cancelling the contract, and about the damage of the purchased object in without omission, because he decided that he is not such purchaser's hand responsible except if he gained from the damage then he is responsible according to the benefit gained by the damage.